Ospital di Baler a health emergency and disaster response facility - Geromo, Michael P. (College of Architecture, University of the Philippines Diliman, 2019)
This study aims to improve the situation of health and disaster resiliency of isolated communities, especially those that frequently suffer from disasters. While there are present problems on health accessibility, disasters do not only destroy infrastructures but also putting the health and safety of people at risk. To improve survivability in times of peace and calamity, the cooperation and integration of two separate by connected entities, health and disaster management, are ventured. The study was conducted by researching on the current situation of a specific community, their reactions and operations during disasters, and conceptual plans from both local to worldwide concerned organizations. Using case studies, experiments, and concepts provided by similar researchers, this study produced a health and safety focused design. Thru architectural means, the product of the research was the integration of municipal hospital and evacuation center. To increase survivability, both evacuation spaces and hospitals should not only remain standing but also remain operational, even during emergencies. This reason explains the integration of such building typologies, and the challenges that it brings is answered thru commonalities in operations and needs. Thus, the proposed project aim is to be a place for all matters of health and life security for both peace and calamity.